AUDIT ADMINISTRASI AKADEMIK MAHASISWA UNIT TATA USAHA DI STAI AL BADAR CIPULUS PURWAKARTA: Implikasi Audit terhadap Peningkatan Mutu Layanan Akademik - Hapsoh; Yanuar, Annisa (Expectation: Journal of Islamic Education Management, 2025)
This study is motivated by the importance of effective and high-quality academic administration services in supporting higher education institutions. The main objective of this study is to examine the condition of student academic administration at the Administrative Office of STAI Al Badar Cipulus Purwakarta based on the results of an internal audit. The method employed is an internal audit using a qualitative descriptive approach through documentation review, observation, and interviews. The findings indicate that academic administration planning has been formally established through standard operating procedures and an academic calendar; however, its implementation has not been optimal due to limitations in the academic information system. Service implementation faces challenges related to students’ understanding of procedures, limited human resources, and insufficient integration of academic data management. Nevertheless, supervision and evaluation mechanisms are conducted regularly and utilized as a basis for service improvement. Overall, the quality of academic administration services requires strengthening in system integration, human resources, and procedural consistency to enhance student academic services.